Peran Etika Bisnis Islam dalam Keputusan Investasi di Lembaga Keuangan Syariah - Nandar Hermawan (Jurnal Inovasi Ekonomi Syariah dan Akuntansi, 2025)
This research analyzes the role of Islamic business ethics in investment decisions in Islamic financial institutions. The background is the rapid growth of the Islamic economy, so that Islamic values such as the prohibition of riba/gharar/maisir, fairness, and transparency become important as a foundation for fair and sustainable investmentsfile. The objective is to explore how sharia principles influence the selection process and investment decisions. The method used is a comprehensive literature study, with literature analysis from books, journals, and academic publications related to Islamic economics. The main findings show that Islamic financial institutions incorporate Islamic ethical values into their investment practices: Islamic banks exercise supervision by the Sharia Supervisory Board and specific codes of conduct; Islamic mutual funds and capital markets apply screening through the Sharia Securities List and DSN-MUI fatwas; Islamic fintech refers to DSN fatwas and emphasizes transparency of fees as well as fairness of return distribution. In conclusion, the integration of Islamic ethical values in the investment process helps build a sustainable and fair Islamic investment system, by emphasizing honesty, fairness and social responsibility in every investment decision.